COMPARATIVE HISTOLOGICAL AND HISTOCHEMICAL STUDY OF THE PAROTID GLAND IN BUFFALOES AND COWS - Adel Jabbar Hussein; Rana Imad Younis (Basrah Journal of Veterinary Research)
The present work designed to describe the histological and histochemical features of parotid gland in buffaloes and cows.The glands were collected from ten heads of buffaloes and cows used. The histological and histochemical study revealed that the parotid gland in buffaloes and cows are compound tubuloacinar-type, having dense connective tissue capsule, the parenchyma consists of acini, intercalated, striated and excretory duct, acini surrounded by myoepithelial cells.The parotidis a purely serous gland. histochemical study,demonstrated of mucopolysaccharide by using combined AB-PAS, acini shows weak to moderate reaction in buffaloes but weak reaction in cows.